2014
DOI: 10.1108/ijwhm-07-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of occupational health checks for hospital employees

Abstract: Purpose – The purpose of this paper is to ascertain which employees choose to access occupational health checks (OHCs), their perceptions of the usefulness of information received and whether they choose to act on tailored advice provided. Design/methodology/approach – In total, 253 hospital employees attended workplace OHC then completed online questionnaire survey. Findings – Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Although workplace health initiatives take many forms, most employers did not provide any form of general health check for their employees even though GHCs have been shown to be feasible and wellaccepted. 17,33 Those that do provide health tests are more likely to be large organisations (rather than SMEs), offering brief tests of usually 15-30 minutes incorporated within a wider health and wellbeing programme. Where GHCs are offered, they generally focus on assessing risk factors for chronic disease, most commonly including weight, BMI, and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although workplace health initiatives take many forms, most employers did not provide any form of general health check for their employees even though GHCs have been shown to be feasible and wellaccepted. 17,33 Those that do provide health tests are more likely to be large organisations (rather than SMEs), offering brief tests of usually 15-30 minutes incorporated within a wider health and wellbeing programme. Where GHCs are offered, they generally focus on assessing risk factors for chronic disease, most commonly including weight, BMI, and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence for longer-term behavioural changes resulting from GHCs is limited 16 , employees value the investment of the organisation in their health and wellbeing and they are accessed by individuals with diverse socio-demographic characteristics and occupational roles. 17 Indeed, the workplace may be a useful platform for reaching individuals reporting risk factors for disease, 17 and other 'high-risk' or vulnerable groups including those with limited access to primary health care or subcultural inertia with respect to anticipatory healthcare. 18 Workplace HIV testing has been utilised in regions of the world where HIV prevalence is particularly high (especially sub-Saharan Africa) and within key sectors (such as mining, military, police, transport and healthcare organisations) that employ population groups that may be particularly vulnerable to HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Data from controlled and uncontrolled studies has revealed workplace HWB services can maintain good health status among employees over the long-term [ 25 ] and deliver significant changes in alcohol consumption, nutrition, sleep, stress, body mass index, depression and perceptions of general health [ 26 28 ], including some long-term improvements in body mass, waist circumference, blood pressure and lipid profiles compared to controls [ 29 ]. Several studies have also reported positive outcomes of workplace HWB services delivered in the NHS, including long-term changes to physical activity (in and out of work), significantly lower sickness absence, greater job satisfaction and greater organisational commitment [ 30 34 ]. Whilst this body of research has demonstrated the potential value of workplace HWB services to the NHS the implementation of these programmes remains a challenge, with few examples nationally.…”
Section: Introductionmentioning
confidence: 99%
“…The workplace is a strategically important platform for promoting public health [ 3 ]. Prior research demonstrates the viability of the workplace setting for delivery of health promotion [ 4 , 5 , 6 ] and health screening [ 7 , 8 , 9 ]. However, in the United Kingdom (UK), sexual health is rarely included in workplace health programs [ 10 ] and the inclusion of HIV testing in workplace health promotion initiatives remains highly innovative.…”
Section: Introductionmentioning
confidence: 99%